Performance of hybrid subsurface constructed wetland system for piggery wastewater treatment - Zhang, X (Water science and technology : a journal of the International Association on Water Pollution Research, 2016)
The objective of this study was to evaluate performance of a hybrid constructed wetland (CW) built for high organic content piggery wastewater treatment in a cold region. The system consists of four vertical and one horizontal flow subsurface CWs. The wetland was built in 2009 and water quality was monitored from the outset. Average purification efficiency of this system was 95±5, 91±7, 89±8, 70±10, 84±15, 90±6, 99±2, and 93±16% for biochemical oxygen demand (BOD5), chemical oxygen demand (COD), total carbon (TC), total nitrogen (TN), ammonium-N (NH4-N), total phosphorus (TP), total coliform (T. Coliform), and suspended solids (SS), respectively during August 2010-December 2013. Pollutant removal rate was 15±18 g m(-2) d(-1), 49±52 g m(-2) d(-1), 6±4 g m(-2) d(-1), 7±5 g m(-2) d(-1), and 1±1 g m(-2) d(-1) for BOD5, COD, TN, NH4-N, and TP, respectively. The removal efficiency of BOD5, COD, NH4-N, and SS improved yearly since the start of operation. With respect to removal of TN and TP, efficiency improved in the first three years but slightly declined in the fourth year. The system performed well during both warm and cold periods, but was more efficient in the warm period. The nitrate increase may be attributed to a low C/N ratio, due to limited availability of carbon required for denitrification